The perspectives of the North-Atlantic Alliance - Dincă, Marian ("Nicolae Bălcescu" Land Forces Academy Publishing House, 2023)
Since its appearance in 1949, NATO has gradually transformed from a collective defense organization into a community providing security. NATO has been and will continue to remain a vital security commitment between Europe and the U.S., equally appreciated by both parties. The Alliance’s evolutionary perspectives equally interested its members and nonetheless other important players in world geopolitics. Currently, NATO is involved in a wide range of activities designed to promote cooperation with a number of countries outside NATO and pro-actively tackle new security challenges of the XXI century. The most relevant aspect of NATO transformation is focused on promoting enhanced political dialogue, both within the organization and in relation with its partners.